PENGARUH BIMBINGAN ORANG TUA TERHADAP PRESTASI BELAJAR PESERTA DIDIK PADA MATA PELAJARAN PENDIDIKAN AGAMA ISLAM DI SMP NEGERI 2 PALENGAAN PAMEKASAN TAHUN PELAJARAN 2022-2023 - Fitriyah, Dianatul; Kulsum, Ummu (Fakultas Agama Islam Universitas Islam Madura, 2024)
The higher the parent's education level, the higher their role in the family's (children's) education. Thus, the influence of parental education level on student learning achievement at SMP Negeri 2 Palengaan Pamekasan is interesting to study and research. The approach used in this research is quantitative with technical product moment formula analysis. The number of samples used was 50 students. The research results can state that there is an influence of parental guidance on students' learning achievement in Islamic religious education subjects at SMP Negeri 2 Palengaan Pamekasan for the 2022-2023 academic year. which can be concluded from the results of data analysis which obtained a figure of 0.68 from 50 samples. These results were compared with the